Detecting leaf water content using intensity data from terrestrial laser scanner - Zhu, Xi (2020)
Leaf water content (LWC) plays an important role in agriculture and forestry management. It can be used to assess drought conditions and wildfire susceptibility [1] . Recent studies have also shown the potential of using terrestrial laser scanner ( TLS ) radiometric information (backscatter intensity) for estimating LWC. The usefulness of backscatter intensity data has been limited by leaf surface characteristics, and incidence angle effects.